Screening for obstructive sleep apnea in atrial fibrillation patients at their home before catheter ablation using watch peripheral arterial tonometry. (25th November 2020) - Tanaka, N; Inoue, K; Tanaka, K; Hirao, Y; Oka, T; Okada, M; Yoshimoto, I; Onishi, T; Iwakura, K; Fujii, K
Abstract: Background: Catheter ablation of atrial fibrillation (AF) is effective, but certain patients experience AF recurrences. Obstructive sleep apnea (OSA) is a risk factor for AF recurrence. Watch peripheral arterial tonometry (WP) has a good correlation with polysomnography (PSG) in terms of the apnea-hypopnea index (AHI) and is easier to perform than PSG. Patients in AF have a high prevalence of OSA. Whether all patients with AF should be evaluated for OSA before catheter ablation is still controversial. Purpose: To elucidate the prevalence and predictors of OSA using WP as a home sleep apnea test in AF patients before catheter ablation. Methods: This study was conducted under a retrospective, single-center, observational design. Patients who received AF ablation without a prior diagnosis of sleep apnea and assessment of their AHI using WP were included in this analysis. The patients were mounted with a WP device by themselves at their own home. Twenty-two patients who were already diagnosed with OSA were excluded. Results: Seven hundred seventy-four (65±11 years, 567 males, 440 paroxysmal AF) out of 776 patients were successfully mounted with WP devices on their own and underwent an OSA assessment. Their mean body mass index (BMI) was 24.1±3.5 kg/m 2 . The mean AHI was 20.1±15.6. Only 88 (11.4%) patients had a normal AHI (AHI<5). Mild OSA (5≤AHI<15), moderate OSA (15≤AHI<30), and severe OSA (AHI≥30) were observed in 274 (35.4%), 252 (32.6%), and 160 (20.7%) patients, respectively. A BMI≥25 (odds ratio [OR]; 2.42, 95% confidence interval [CI]; 1.74–3.37, p<0.001), male sex (1.70, 1.19–2.44, p=0.0037), non-paroxysmal AF (1.90, 1.35–2.66, p=0.0002), hypertension (1.70, 1.24–2.33, p=0.009), and left atrial volume index ≥30 (OR=1.51, CI 1.06–2.16, p=0.022) were significant predictors of moderate or severe OSA by a multivariate analysis, while an Epworth sleepiness scale ≥11 was not a predictor of moderate or severe OSA (OR=0.99, CI 0.66–1.49, p=0.95). However, 44.2% of non-obese patients (BMI <25) had moderate-severe OSA. Conclusion Almost: All patients successfully underwent WP to diagnose OSA. AF patients had a high prevalence of OSA, and screening OSA would be important in AF patients receiving ablation even if patients do not have sleepiness or are obese. We cannot deny OSA in AF patients before catheter ablation without performing screening tests for OSA. Funding Acknowledgement: Type of funding source: None